Identifying Experiences and Hopelessness Levels of Women Receiving Infertility Treatment: A Mixed Method Study* - Citil Canbay, Funda; citil, Elif Tugce; Sadiye Citil Sap, Tugba; Sap, Osman (Routledge Journals, Taylor & Francis Ltd, 2022)
The research aimed to identify experiences and hopelessness levels of women receiving infertility treatment. The quantitative sample included 276 women receiving infertility treatment at a university hospital and structured interviews were done with 20 women in qualitative dimension. It was identified that socio-demographic factors, knowledge about infertility treatment, alternative treatment tendencies and use of plant cures affected hopelessness levels (p<.05). Four themes were found in the qualitative dimension about infertility and treatment process It was seen that Turkish women did not have sufficient knowledge about the process of infertility and treatment and had a high level of hopelessness.
Keywords: Infertility; women; hopelessness; experience; Turkey